Hypernudging in the Digital Era: Exploring the Impact and Ethical Considerations of Advanced Behavioral Interventions - Apriliani, Lydia (UPY Business and Management Journal (UMBJ), 2025)
Purpose: This conceptual review explores the phenomenon of “hypernudging” advanced, algorithm-driven behavioral interventions in digital environments. It aims to distinguish hypernudging from traditional nudging, assess its ethical implications, and propose a comparative framework to guide future research. Design/methodology/approach: The study uses a conceptual narrative review method, drawing on interdisciplinary literature from behavioral economics, digital governance, and information systems. Findings: Hypernudging introduces a unique form of behavioral influence marked by personalization, algorithmic opacity, and real-time adaptability. While enhancing digital decision-making efficiency, it challenges core ethical principles such as transparency, autonomy, and accountability. Originality/value: This paper contributes by introducing a novel comparative matrix differentiating nudging types and proposing an ethical evaluation lens based on autonomy theory and algorithmic accountability. Limitations: This paper is limited to a conceptual nature; future empirical validation is needed in real-world digital contexts and across diverse populations. Practical implications: Understanding hypernudging can guide digital marketers, policy designers, and technology developers to ethically design interventions that respect user autonomy while effectively influencing decision-making in digital spaces.